Psychosocial factors in nursing work and occupational risks: a systematic review - Patrícia Carneiro Pessoa Pousa; Sérgio Roberto de Lucca (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objective: to identify, in international scientific production, the main psychosocial factors in nursing work, found through the Copenhagen Psychosocial Questionnaire (COPSOQ) application. Methods: a systematic review study of psychosocial factors at work among nursing professionals, who used COPSOQ in the assessment of work environments. Results: fifteen articles were identified, which highlighted as main psychosocial dimensions of nursing work demands, work organization, social relationships and leadership, work-home interface, workplace health and well-being and offensive behaviors. Conclusion: the high demands for cognitive, emotional work and work pace were identified in the nursing routine. Management support had a positive impact. Physical and psychological violence and shift work interfere in family life, aggravating the fatigue of these professionals. Interventions for reducing work stress presuppose the identification of psychosocial factors involved in nursing work.